FINANCIAL LITERACY AND FINANCIAL ATTITUDE IN PREDICTING FINANCIAL MANAGEMENT PERFORMANCE: EVIDENCE FROM EMPLOYEES OF PT BANK SULSELBAR MAKASSAR - Muhammad Umar Data; Nurul Alifya; Elyas Albar (Universitas Nusa Cendana, 2026)
This study aims to examine the effect of financial literacy and financial attitude on financial management performance among employees of PT Bank Sulselbar in Makassar. The research adopts a quantitative approach using a survey method, with data collected through questionnaires distributed to employees. The collected data were analyzed using multiple linear regression. The results indicate that financial literacy does not significantly influence financial management performance. Similarly, financial attitude also does not show a significant effect on financial management performance. When examined simultaneously, financial literacy and financial attitude together do not significantly affect financial management performance. These findings suggest that financial knowledge and attitudes alone are not sufficient to explain variations in individuals’ financial management performance. Other factors, such as financial behavior, income level, and financial discipline, may play a more important role in shaping effective financial management practices among employees. Keywords: Financial Literacy; Financial Attitude; Financial Management Performance